2016
DOI: 10.4236/ojvm.2016.62004
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Bovine Parainfluenza Virus Type 3 (bPI-3V) in Ruminants from Grenada

Abstract: Respiratory viral infections are known for serious economic losses in ruminants. Bovine parainfluenza 3 virus (bPI-3V) a member of Respirovirus genus in association with other respiratory viruses causes respiratory disease complex in ruminants. The aim of this study was to estimate the seroprevalence of bPI-3V in non vaccinated cattle, sheep and goats from Grenada. Sera were collected randomly from 60 sheep, 60 goats and 60 cattle from all six parishes of Grenada. Sera were tested for antibodies to bPI-3V usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
(15 reference statements)
0
9
0
1
Order By: Relevance
“…Ceribasi et al (2014) and Yener et al (2005) detected PI-3 positivity in bronch cartilage tissue in cattle and goats, and in the study, PI-3 antigen was found in bronch cartilage in both sheep and goats. PCR, Culture, Virus Isolation, Electron Microscopy, DFAT, IFAT, and IP techniques are used to determine the prevalence of RSV and PI-3 virus in naturally infected flocks in our country and in the World (Emikpe et al, 2019;Jarikre and Emikpe, 2017;Sharma et al, 2017;Tiwari et al, 2016). In previous studies, the immunohistochemical method (IHC) was used to determine the presence of RSV and PI-3 antigen in respiratory tract infections of ruminants and their distribution in the lung (Ceribasi et al, 2013;Haines et al, 1992;Yener et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceribasi et al (2014) and Yener et al (2005) detected PI-3 positivity in bronch cartilage tissue in cattle and goats, and in the study, PI-3 antigen was found in bronch cartilage in both sheep and goats. PCR, Culture, Virus Isolation, Electron Microscopy, DFAT, IFAT, and IP techniques are used to determine the prevalence of RSV and PI-3 virus in naturally infected flocks in our country and in the World (Emikpe et al, 2019;Jarikre and Emikpe, 2017;Sharma et al, 2017;Tiwari et al, 2016). In previous studies, the immunohistochemical method (IHC) was used to determine the presence of RSV and PI-3 antigen in respiratory tract infections of ruminants and their distribution in the lung (Ceribasi et al, 2013;Haines et al, 1992;Yener et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations have been carried out with serological tests such as Virus Neutralization Test (VNT), ELISA, Immunofluorescent Antibody (IFA) and Hemagglutination Inhibition (HI) for the prevalence of ruminant RSV and PI-3 agents (Franco et al, 2020;Tiwari et al, 2016). Immunohistochemical (IHC), Immunofluorescence (IF), Direct Fluorescent Antibody Technique, and Electron Microscope methods are currently used in the lung tissue of ruminant animals to show detailed RSV and PI-3 viruses (Aniță et al, 2015;Jarikre and Emikpe, 2017).…”
mentioning
confidence: 99%
“…[9] reported higher infection in cows older than 5 years of age. BPI-3V is in the genus Respirovirus of the family Paramyxoviridae [10], which cause serious economic losses in small and large ruminants. Clinical disease is usually mild, with symptoms of fever, nasal discharge, and cough [11].…”
Section: Introductionmentioning
confidence: 99%
“…BPIV-3, Paramyxoviridae ailesinde Respirovirus cinsinde yer almaktadır. 12 Tek başına hafif seyirli enfeksiyon oluşturan virus, alveolar epitel ve makrofajların yanı sıra üst ve alt solunum yollarındaki siliyer solunum epitel hücrelerini de enfekte etmektedir. Etken sığırlarda görülmekle birlikte, tüm dünyada koyun ve keçilerin solunum yollarında sık rastlanan viral etkenlerden biridir.…”
unclassified